Comparative analysis of disaster management between India and Nigeria - Shakeri, Ehsan; Vizvâri, Bêla; Nazerian, Ramtin (Elsevier Ltd, 2021)
This paper reviews, compares, and analyzes the legal and institutional frameworks of the Disaster Management (DM) systems in India and Nigeria. This research aims to study the effectiveness and efficacy of the DM systems in both countries to identify the strengths and weaknesses and make recommendations for enhancing the current systems. The study initially provides a comprehensive introduction of Indian and Nigerian DM systems, including the countries' disaster profiles and the current DM policies and institutional frameworks, then compares them from various perspectives to identify the similarities, differences, common challenges, and lessons learned. An intense documentary survey of relevant literature is applied in this study to obtain data and information. The study finds that India, by developing better legal and institutional frameworks, creates a more effective DM system than Nigeria in terms of the integration and prioritization of Disaster Risk Reduction (DRR) efforts, community participation and coordination, and collaboration mechanisms. The research also discovers that both nations struggle to mobilize, manage, and utilize DM funds due to a lack of transparency in funding sources, particularly at the state and local/district levels. The findings also show that both countries’ DM systems are mainly focused on natural disasters, with little emphasis provided on effective preventative and regulatory measures to deal with the risks and consequences of man-made hazards. The paper concludes that due to administrative and financial issues, none of the two countries achieved total success in capacity building activities. © 2021 Elsevier Ltd
Keywords: Disaster management system; Disaster risk reduction; Indian disaster management; Man-made disaster management; Natural disaster management; Nigerian disaster management